Nucleation, Growth, and Alignment of Poly(3-hexylthiophene) Nanofibers for High-Performance OFETs - Persson, Nils E; Chu, Ping-Hsun; McBride, Michael; Grover, Martha; Reichmanis, Elsa (Accounts of chemical research, 2017)
Conjugated semiconducting polymers have been the subject of intense study for over two decades with promising advances toward a printable electronics manufacturing ecosystem. These materials will deliver functional electronic devices that are lightweight, flexible, large-area, and cost-effective, with applications ranging from biomedical sensors to solar cells. Synthesis of novel molecules has led to significant improvements in charge carrier mobility, a defining electrical performance metric for many applications. However, the solution processing and thin film deposition of conjugated polymers must also be properly controlled to obtain reproducible device performance. This has led to an abundance of research on the process-structure-property relationships governing the microstructural evolution of the model semicrystalline poly(3-hexylthiophene) (P3HT) as applied to organic field effect transistor (OFET) fabrication. What followed was the production of an expansive body of work on the crystallization, self-assembly, and charge transport behavior of this semiflexible polymer whose strong π-π stacking interactions allow for highly creative methods of structural control, including the modulation of solvent and solution properties, flow-induced crystallization and alignment techniques, structural templating, and solid-state thermal and mechanical processing. This Account relates recent progress in the microstructural control of P3HT thin films through the nucleation, growth, and alignment of P3HT nanofibers. Solution-based nanofiber formation allows one to develop structural order prior to thin film deposition, mitigating the need for intricate deposition processes and enabling the use of batch and continuous chemical processing steps. Fiber growth is framed as a traditional crystallization problem, with the balance between nucleation and growth rates determining the fiber size and ultimately the distribution of grain boundaries in the solid state. Control of nucleation can be accomplished through a sonication-based seeding procedure, while growth can be modulated through supersaturation control via the tuning of solvent quality, the use of UV irradiation or through aging. These principles carry over to the flow-induced growth of P3HT nanofibers in a continuous microfluidic processing system, leading to thin films with significantly enhanced mobility. Further gains can be made by promoting long-range polymer chain alignment, achieved by depositing nanofibers through shear-based coating methods that promote high fiber packing density and alignment. All of these developments in processing were carried out on a standard OFET platform, enabling us to generalize quantitative structure-property relationships from structural data sources such as UV-vis, AFM, and GIWAXS. It is shown that a linear correlation exists between mobility and the in-plane orientational order of nanofibers, as extracted from AFM images using advanced computer vision software developed by our group. Herein, we discuss data-driven approaches to the determination of process-structure-property relationships, as well as the transferability of structural control strategies for P3HT to other conjugated polymer systems and applications.